2022
DOI: 10.3389/fonc.2022.983254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osteoblast-derived extracellular vesicles on aggressiveness, redox status and mitochondrial bioenergetics of MNNG/HOS osteosarcoma cells

Abstract: Osteosarcoma is the most common primary bone malignancy. The crosstalk between osteosarcoma and the surrounding tumour microenvironment (TME) drives key events that lead to metastasization, one of the main obstacles for definitive cure of most malignancies. Extracellular vesicles (EVs), lipid bilayer nanoparticles used by cells for intercellular communication, are emerging as critical biological mediators that permit the interplay between neoplasms and the tumour microenvironment, modulating re-wiring of energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Studies have shown that nanoparticles can regulate Tregs and MDSCs, boost T cell responses, and extend survival in cancer models. 84 For example, nanoparticles have been used to co-deliver checkpoint inhibitors and cytokines or combined with CD28-binding aptamers to activate T cells while suppressing Tregs, resulting in significant tumor growth inhibition. 85 Nanoliposome-delivered curcumin effectively suppresses Tregs and boosts CD8+ T cell responses in melanoma and breast cancer.…”
Section: Immune Cell Interaction With Tumorsmentioning
confidence: 99%
“…Studies have shown that nanoparticles can regulate Tregs and MDSCs, boost T cell responses, and extend survival in cancer models. 84 For example, nanoparticles have been used to co-deliver checkpoint inhibitors and cytokines or combined with CD28-binding aptamers to activate T cells while suppressing Tregs, resulting in significant tumor growth inhibition. 85 Nanoliposome-delivered curcumin effectively suppresses Tregs and boosts CD8+ T cell responses in melanoma and breast cancer.…”
Section: Immune Cell Interaction With Tumorsmentioning
confidence: 99%
“…OBs can affect the formation, differentiation, or apoptosis of osteoclasts (OCs) through several pathways, including the OPG/RANKL/RANK, RANKL/LGR4/RANK, Ephrin2/ ephB4, and Fas/FasL pathways [27]. OBs communicate with OS through OB-derived extracellular vesicles (OB-EVs) to regulate the TME of OS [28].…”
Section: Osteoblast Cellsmentioning
confidence: 99%